Belonging in Brexit Britain: Central and Eastern European 1.5 generation young people's experiences. Issue 1 (24th October 2018) - Tyrrell, Naomi; Sime, Daniela; Kelly, Claire; McMellon, Christina
Abstract: In this paper, we examine the experiences of young people born in Central and Eastern Europe (CEE) who are part of the 1.5 migrant generation living in "Brexit Britain." We focus on two key themes: (a) young people's feelings of belonging to Britain, their countries of birth and Europe, and the ways in which these have been impacted by the EU Referendum result; (b) young people's future plans, in an intergenerational context, with particular regard to their feelings of belonging and the ruptures of migration and Brexit. Britain's decision to leave the EU caused uncertainty for CEE 1.5 generation young people at a time when many of them were consciously reflecting on their beings, becomings, and belongings. The majority of young people asserted a sense of belonging to Britain whilst simultaneously feeling a sense of "in‐between‐ness." Many young people wanted to remain living in Britain, at least in the short term, and felt a sense of belonging to Britain. Our focus on the potential intergenerational impact of Brexit suggests that CEE young people and parents may view possibilities for the future differently; we examine some of the key reasons for these differences from the young people's perspectives.